Isoprene Responses and Functions in Plants Challenged by Environmental Pressures Associated to Climate Change - Fini, Alessio; Brunetti, Cecilia; Loreto, Francesco; Centritto, Mauro; Ferrini, Francesco; Tattini, Massimiliano (Frontiers in Plant Science, 2017)
The functional reasons for isoprene emission are still a matter of hot debate. It was hypothesized that isoprene biosynthesis evolved as an ancestral mechanism in plants adapted to high water availability, to cope with transient and recurrent oxidative stresses during their water-to-land transition. There is a tight association between isoprene emission and species hygrophily, suggesting that isoprene emission may be a favorable trait to cope with occasional exposure to stresses in mesic environments. The suite of morpho-anatomical traits does not allow a conservative water use in hygrophilic mesophytes challenged by the environmental pressures imposed or exacerbated by drought and heat stress. There is evidence that in stressed plants the biosynthesis of isoprene is uncoupled from photosynthesis. Because the biosynthesis of isoprene is costly, the great investment of carbon and energy into isoprene must have relevant functional reasons. Isoprene is effective in preserving the integrity of thylakoid membranes, not only through direct interaction with their lipid acyl chains, but also by up-regulating proteins associated with photosynthetic complexes and enhancing the biosynthesis of relevant membrane components, such as mono- and di-galactosyl-diacyl glycerols and unsaturated fatty acids. Isoprene may additionally protect photosynthetic membranes by scavenging reactive oxygen species. Here we explore the mode of actions and the potential significance of isoprene in the response of hygrophilic plants when challenged by severe stress conditions associated to rapid climate change in temperate climates, with special emphasis to the concomitant effect of drought and heat. We suggest that isoprene emission may be not a good estimate for its biosynthesis and concentration in severely droughted leaves, being the internal concentration of isoprene the important trait for stress protection.